PEMIKIRAN PENDIDIKAN ISLAM MENURUT SUNAN KALIJAGA - Zahrowiyah, Siti; Sakurin, Siti Aimatus; Utari, Susi; Zubaedah, Siti; Nurbayanti, Siti; Sofari, Sofari (STAI Darul Qalam Tangerang, 2025)
Education plays an important role in this life, all activities carried out by humans are educational processes, in this discussion it will be more specific to Islamic education, as we know now moral decline is happening everywhere, students also seem to be accustomed to doing immoral actions such as brawls between students to being involved in drug problems. This can actually be predicted by education practitioners, because the education that exists today emphasizes its students more on their cognitive abilities without being accompanied by abilities in the affective field, so here we will review Islamic education, which in this case will later be known what kind of Islamic education can at least make students return to their nature, namely as caliphs on this earth. Departing from that background, the author then wants to discuss it in the thesis and takes the title Islamic Educational Thoughts According to Sunan Kalijaga. Departing from that, the author then wants to discuss the thoughts of Indonesian Muslim figures and intellectuals who try to formulate Islamic education that is in accordance with the scope of religion, nation and state, such as Sunan Kalijaga. Hopefully, the education that he has taught and passed on to the Indonesian nation will be able to inspire elements implementing education in order to develop Islamic education so that Islamic education will be able to answer the challenges of globalization while still being based on the values ​​of Islamic teachings. The focus of the problem in this study is the concept of education according to Sunan Kalijaga, as well as Sunan Kalijaga's contribution in the field of education. From the focus of the problem that has been mentioned earlier, the author took steps to then analyze or research it with the aim of being able to know, understand, and be able to draw conclusions from Sunan Kalijaga's Islamic educational thoughts, so that the results of the study can be used as a contribution to the implementation and development of Islamic education. This study uses a qualitative descriptive approach with the type of library research. While the data collection method uses the documentation method in order to find sources and data that support this writing. Then from the documentation it is analyzed using the content analysis method and interpretation of the sources and data obtained. The results of the research conducted by the author can be presented here after reviewing Sunan Kalijaga's thoughts on education not only enjoyed by the nobility, the concept of education that he has taught has an important role for a prospective teacher, and combines education and culture as a solution to teaching Islamic education that is easily accepted by all groups. Education is adjusted to the conditions of society, with an approach that is appropriate to society. Sunan Kalijaga's contribution to Islamic education in Indonesia is very much. With his thoughts on the acculturation of education and culture. And until now this culture is still preserved by the community.